Ultrasound fusion imaging with real-time navigation for the surveillance after endovascular aortic aneurysm repair - Joh, Jin Hyun (Ann Surg Treat Res, 2017)
Ultrasound can be an effective alternative to computed tomography for surveillance following endovascular aneurysm repair (EVAR). Recently, ultrasound fusion imaging with the real-time navigation system was introduced. Here we described 3 patients who underwent post-EVAR surveillance using this novel technique. Complete coregistration was achieved in all patients. The origin of left renal artery was selected for the target of coregistration. Ultrasound fusion imaging was useful to differentiate the confusing lesion and to evaluate the complete resolution of endoleak and newly developed delayed endoleak. Ultrasound fusion image with real-time navigation system can be a feasible imaging tool for post-EVAR surveillance.